Adherence to the World Cancer Research Fund/American Institute for Cancer Research recommendations and breast cancer risk. Issue 11 (19th February 2016) - Harris, Holly R.; Bergkvist, Leif; Wolk, Alicja
Abstract : The World Cancer Research Fund/American Association for Cancer Research (WCRF/AICR) has published eight nutrition‐related recommendations for the prevention of cancer. However, few prospective studies have examined these recommendations by breast cancer hormone receptor subtype and only one case–control study has included the dietary supplements recommendation in their evaluation. We investigated whether adherence to the WCRF/AICR cancer prevention recommendations was associated with breast cancer incidence, overall and by hormone receptor subtype, in the Swedish Mammography Cohort. Among 31, 514 primarily postmenopausal women diet and lifestyle factors were assessed with a self‐administered food frequency questionnaire. A score was constructed based on adherence to the recommendations for body fatness, physical activity, energy density, plant foods, animal foods, alcoholic drinks and dietary supplements (score range 0–7). Cox proportional hazard models were used to calculate hazard ratios (HRs) and 95% confidence intervals (95% CIs). During 15 years of follow‐up 1, 388 cases of breast cancer were identified. Women who met six to seven recommendations had a 51% decreased risk of breast cancer compared to women meeting only zero to two recommendations (95% CI = 0.35–0.70). The association between each additional recommendation met and breast cancer risk was strongest for the ER‐positive/PR‐positive subtype (HR = 0.86; 95% CI = 0.79–0.94), while for the ER‐negative/PR‐negative subtype the individual recommendations regarding plant and animal foods were most strongly associated with reduced risk. Our findings support that adherence to the WCRF/AICR recommendations reduces breast cancer risk in a population of primarily postmenopausal women. Promoting these recommendations to the public could help reduce breast cancer incidence. Abstract : What's new? Adherence to the nutrition‐related recommendations for cancer prevention introduced in 2007 by the World Cancer Research Fund/American Association for Cancer Research (WCRF/AICR) is linked to overall reductions in cancer incidence and mortality. It remains uncertain, however, whether adherence to the recommendations reduces breast cancer incidence specifically. In this study, women who met all or nearly all of the WCRF/AICR recommendations benefited from a 51 percent decrease in breast cancer risk compared to women who met none or only a couple of the recommendations. The association with risk reduction was strongest for ER‐positive/PR‐positive breast tumors.